2013
DOI: 10.1248/bpb.b12-00655
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Astragaloside IV on Action Potentials and Ionic Currents in Guinea-Pig Ventricular Myocytes

Abstract: Astragaloside IV (AS-IV) is one of the main active constituents of Astragalus membranaceus, which has various actions on the cardiovascular system. However, its electrophysiological mechanisms are not clear. In the present study, we investigated the effects of AS-IV on action potentials and membrane currents using the whole-cell patch clamp technique in isolated guinea-pig ventricular myocytes. AS-IV prolonged the action potential duration (APD) at all three tested concentrations. The peak effect was achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…Thus these pharmacological effects of AS-IV may be related with its effects on L-type Ca 2 þ channel activity. Previously, we have reported that, AS-IV affects the action potential and one of its effective targets may be the L-type Ca 2 þ channels (Zhao et al, 2013). In the present study, we provided direct evidence that AS-IV affected peak current amplitude of Ca 2 þ current.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Thus these pharmacological effects of AS-IV may be related with its effects on L-type Ca 2 þ channel activity. Previously, we have reported that, AS-IV affects the action potential and one of its effective targets may be the L-type Ca 2 þ channels (Zhao et al, 2013). In the present study, we provided direct evidence that AS-IV affected peak current amplitude of Ca 2 þ current.…”
Section: Discussionsupporting
confidence: 73%
“…It can be used as potential therapeutic intervention in cardiovascular diseases (Fu et al, 2011(Fu et al, ,2014Yang et al, 2012). AS-IV, one of the major active components of A. membranaceus, is a potent blocker of L-type Ca 2 þ channels in guinea-pig ventricular myocytes (Zhao et al, 2013). In this study, we explored the electrophysiological mechanisms of I CaL inhibition by AS-IV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Astragaloside IV, the component of Astragalus membranaceus, exhibits anti-oxidant, anti-cancer and neuro-protective properties [16]. In the current study, we investigated the tumor suppressive effects of astragaloside IV combined with B7-H3 in NSCLC cells.…”
Section: Introductionmentioning
confidence: 99%